Família rural e produção de tabaco: estratégias de reprodução social em Arroio do Tigre/RS - Redin, Ezequiel (2015)
The overall aim of the thesis was to understand the social reproduction of tobacco growing families and the experiences lived in the different times of rural development in the town of Arroio do Tigre / RS. The research was a case study. For its conduction, we used both literature and secondary sources as observations and interviews in fieldwork. The theoretical framework centered on the concepts of Pierre Bourdieu's theory on strategies of social reproduction and habitus in particular. Based on the literature on colonization, rural family, social reproduction in tobacco farming, we aimed to describe and analyze changes in the rural area and the difficulties of families in the farm, paying attention to subjective aspects of family relationship, integration system, the farmer on the expansion of spaces of sociability and market, and the changes in the forms of production and reproduction in the countryside. We held thirty-one semi-structured interviews with farmers and rural youth of the town and a number of complementary informal talks. Among the results that are worth mentioning, we identified four phases in the constitution of rural households and tobacco expansion in the town: Phase I the tobacco craft production: from the beginning of the colonization to the 1960s, when the settlers, descendants from German and Italian immigrants, consolidated the region as a major producer of tobacco and installed the tobacco culture as part of the tradition of production systems, using it as a motto for the town‟s emancipation, reproducing the logic of the economic system in the countryside; Phase II The modern production of tobacco: period from 1960 to 2000, in the strengthening of agro-industrial integration system, in which the rural family had to reorder its rural management, readapt to new technologies imposed by the agro-industrial complex, changing knowledge and its ways to produce and reproduce in the countryside; Phase III tobacco production in evidence: after 2000‟s decade, when different conflicts emerged in the tobacco field; a process of mechanization of tobacco crops begins and impacts on family labor management; women‟s participation spaces are extended in family and production; modernization continues to be of essential importance in productive activity in the rural area; Phase IV The future of the tobacco production and young heirs: between the present and the future, the rural family is tensioned by rural youth and by the state interventions; international mechanisms interfere in the management of rural families, as in the case of child labor; a period of intensification of social relations in the countryside of and intense mobility, which cause tensions between the future of the land and inheritance, besides the technological factor increasingly intense in family farming, which causes a pressure for lands and strong relationship to the economic system. Tobacco was a participant in productive activities of peasants life from a shared knowledge, and the incorporation of the tobacco habitus became an inherited knowledge after hill settlement. The exit of young people does not imply a crisis of social reproduction of rural families and, respectively, the production unit. The history of tobacco and of rural households in the region of Arroio do Tigre is marked by the inherited tradition reproduced there.